Evaluation of antimicrobial activities of Bacillus megaterium with a third-generation cephalosporin (ceftriaxone) - Tu HK Nguyen, Le B Thu (Journal of Applied Pharmaceutical Science, 2015)
Bacillus megaterium T04 isolated from Rach Lang stream in Vietnam was tested for antimicrobial activities. The antimicrobial activities of Bacillus megaterium T04 (57.3x108 cfu/mL) against Candida albicans, Salmonella typhi, Pseudomonas aeruginosa, Staphylococcus sciuri, Micrococcus luteus were detected by agar well diffusion method in different cultivation conditions at three temperatures (25, 37, and 45oC) in three incubation periods (24, 48, and 72 hours). The efficacy of antimicrobial activities of this strain were determined in comparison with ceftriaxone activity against Candida albicans, Salmonella typhi, Pseudomonas aeruginosa, Staphylococcus scuiri, Micrococcus luteus. The antimicrobial activity potency was equivalent to ceftriaxone in a range ( 3.3 0.6 μg/mL to 46.5 6.2 μg/mL) for Candida albicans (0.9 0.2 μg/mL to 35.5 7.7 μg/mL) for Salmonella typhi, (0.4 0.1 μg/mL to 28.4 4.4 μg/mL) for Pseudomonas aeruginosa, (119.8 21.2 μg/mL to 283.7 26.0 μg/mL) for Staphylococcus scuiri, (3.3 0.4 μg/mL to 64.4 7.4 μg/mL) for Micrococcus luteus.
Keywords: Antimicrobial activities, Bacillus megaterium T04, ceftriaxone, potency.